Test-retest reliability of in situ unaided thresholds in adults. - Smith-Olinde L; Nicholson N; Chivers C; Highley P; Williams DK (American Journal of Audiology, 2006)
PURPOSE: The purpose of this study was to examine test-retest reliability of in situ unaided thresholds measured using a handheld hearing aid programmer coupled to a hearing aid transducer in adults with normal hearing. METHOD: Randomized in situ thresholds at 4 octave frequencies were established in 1 ear of 43 adults twice using the Widex Diva SP3 device with the stimulus generated by and transduced through a Widex Diva SD-9 behind-the-ear hearing aid. Insert earphone tips were used in each of the measures to couple the hearing aid/transducer to the ear canal. RESULTS: Mean decibel differences between the test and retest thresholds were less than 1 dB at each frequency. Using an 80% statistical test criterion, results revealed test-retest reliability within 5 dB for all frequencies: 98% at 500 Hz, 100% at 1000 and 2000 Hz, and 93% at 4000 Hz. CONCLUSIONS: Test-retest reliability of in situ unaided thresholds using the SP3/SD-9 device is equivalent to that of currently accepted audiometric procedures.